Experiences and perceptions of the theory‐practice gap in nursing in a resource‐constrained setting: A qualitative description study - Salifu, David Abdulai; Gross, Janet; Salifu, Mohammed Awal; Ninnoni, Jerry PK (Nursing open, 2019)
Aim To describe experiences and perceptions of theory‐practice gap in nursing in a resource‐constrained setting. Theory‐practice gap is extensively discussed and studied in some parts of the world. Interventions to bridge the theory‐practice gap have been varied and depend on an understanding of the contextual healthcare environment. Experiences and perceptions of the theory‐practice gap in a resource‐constrained setting have not been comprehensively described. Design A qualitative description methodology was used. Methods Maximum variation sampling based on role in the events of theory‐practice gap was used to recruit student nurses, nurse faculty and clinicians from two study sites for focus group discussions. Data were analysed using conventional content analysis. Results Five themes were identified: system inadequacies; resource constraints; challenges of the clinical learning environment; clinical placement and supervision; and nurse faculty factors. Systems inadequacy and resource constraints formed the spine of the challenges contributing to the theory‐practice gap in the research setting.